Low Birth Weight as The Risk factor of Coronary Heart Diseases - Wibowo, Joko Wahyu (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Low birth weight, a nutritional deficiency is related to the increased in the coronary heart disease insidence. Low birth weight is correlated with the hipotalamus-pituitary-adrenal responsible for the the concentration of cortisol in sirculation, increased in homosistein, insuline resistence and increased C reactive protein playing role on the aterosclerosis process predispose the corronary disease. This paper will discuss the relationship between the low birth weight and the ateroclesoris process leading to coronary heart disesase (Sains Medika, 3(2):185-200).